Keefektifan Mata Pelajaran Pendidikan Kewarganegaraan dalam Kurikulum MBKM di Kota Jayapura - Yan Dirk Wabiser; Bernarda Meteray (FKIP, Universitas Palangka Raya, 2021)
Civic Education (PKn) has a crucial role in character building and awareness of life as a citizen. This research will analyze the effectiveness of Civics Education in the MBKM curriculum framework in Jayapura City. This research was conducted using a qualitative approach method, based on data collected from interviews, direct observation, and document analysis. The results indicate that the implementation of Civics in the MBKM curriculum in Jayapura City still faces various challenges, but also shows significant potential in increasing student participation in civic activities.